2021
DOI: 10.1108/jbim-04-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the post-harvest supply chain enablers of vertical integration for rural employability and marketability

Abstract: Purpose The purpose of this study is to analyze the post-harvest supply chain enablers (PHSCEs) for vertical integration to enhance rural employability, farmer profitability and rural produce marketability (i.e. market prospects) in the post-harvest supply chain (PHSC). The impact of vertical integration is also explored for various commercial produces. Design/methodology/approach A structural equation modeling (SEM) of PHSCEs for vertical integration was developed to enhance market prospects, rural employab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 75 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Surucu-Balci and Tuna (2021), for instance, explored logistics-related drivers of food loss, and the results of their analytical hierarchy process revealed that warehousing-related factors were key to such loss. Priyadarshi et al. (2022) used fuzzy TOPSIS to explore factors that enabled vertical consolidation in post-harvest agri-food supply chains, the analytical results of which indicated that warehousing played a paramount role in that process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surucu-Balci and Tuna (2021), for instance, explored logistics-related drivers of food loss, and the results of their analytical hierarchy process revealed that warehousing-related factors were key to such loss. Priyadarshi et al. (2022) used fuzzy TOPSIS to explore factors that enabled vertical consolidation in post-harvest agri-food supply chains, the analytical results of which indicated that warehousing played a paramount role in that process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A higher amount of waste has often been observed in longer downstream supply chains. Thus, intermediaries in the supply shall be reduced as much as possible (Villalobos et al, 2019;Priyadarshi et al, 2022aPriyadarshi et al, , 2022b. Establishing local markets, supermarkets and export markets will tend to reduce post-yield losses (Gunasekera et al, 2017).…”
Section: Literature Surveymentioning
confidence: 99%
“…The loss in exports was observed as fresh produce faced temperature stresses in the absence/mismanagement of reefer containers (Bhatnagar et al, 2019). The technique of food processing/value addition eventually increases farmers' revenue by extending the shelf-life of the produce and market prospects (Bhatnagar et al, 2019;Anand and Barua, 2022;Priyadarshi et al, 2022aPriyadarshi et al, , 2022bGaneshkumar et al, 2023). The above types of losses have resulted in revenue losses in PYSC, leading to lesser returns on investment (Bhatnagar et al, 2019;Minten et al, 2021;Anand and Barua, 2022;Akpa et al, 2023;Ganeshkumar et al, 2023).…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations